2007
DOI: 10.1021/bi0622165
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of PshB, the Dicluster Ferredoxin that Harbors the Terminal Electron Acceptors FA and FB in Heliobacterium modesticaldum,

Abstract: The Type I homodimeric photosynthetic reaction center found in anaerobic gram-positive bacteria of the genus Heliobacteriaceae incorporates FA- and FB-like iron-sulfur clusters similar to those found in Photosystem I as terminal electron acceptors. We recently isolated the PshB protein that harbors the iron-sulfur clusters from the reaction centers of Heliobacterium modesticaldum. Here, we report the cloning of a candidate gene and the properties of its product. Genuine PshB was dissociated from the reaction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…In addition to pshA, a pshB gene (HM1_1462), which encodes an RC-associated [4Fe-4S]-binding ferredoxin, was confirmed to be present in the H. modesticaldum genome. A recent study showed that PshB binds the terminal Fe/S dicluster electron acceptors, F A and F B (19). Electrons are likely transferred from the Fe/S clusters to a cytoplasmic ferredoxin, which can supply reducing equivalents for cellular processes, such as carbon assimilation and nitrogen fixation (Fig.…”
Section: Vol 190 2008 Complete Genome Of H Modesticaldum 4693mentioning
confidence: 99%
“…In addition to pshA, a pshB gene (HM1_1462), which encodes an RC-associated [4Fe-4S]-binding ferredoxin, was confirmed to be present in the H. modesticaldum genome. A recent study showed that PshB binds the terminal Fe/S dicluster electron acceptors, F A and F B (19). Electrons are likely transferred from the Fe/S clusters to a cytoplasmic ferredoxin, which can supply reducing equivalents for cellular processes, such as carbon assimilation and nitrogen fixation (Fig.…”
Section: Vol 190 2008 Complete Genome Of H Modesticaldum 4693mentioning
confidence: 99%
“…This effort was aided by an earlier report of the isolation and amino acid sequences of two bacterial dicluster ferredoxins, Fd1 and Fd2, from H. mobilis (Hatano et al 2005). The N-terminal amino acid sequence of Fd2 was seen to be similar to the N-terminal sequence of PshBI from H. modesticaldum (Heinnickel et al 2007). After cloning the pshBI gene (annotated as HM1_1462 in H. modesticaldum) and identifying its location on the H. modesticaldum genome, it became clear that fd2 and pshBI are orthologs (Heinnickel et al 2007).…”
Section: Pshbi and Pshbii The Proteins Harboring The F A And F B Clumentioning
confidence: 65%
“…The N-terminal amino acid sequence of Fd2 was seen to be similar to the N-terminal sequence of PshBI from H. modesticaldum (Heinnickel et al 2007). After cloning the pshBI gene (annotated as HM1_1462 in H. modesticaldum) and identifying its location on the H. modesticaldum genome, it became clear that fd2 and pshBI are orthologs (Heinnickel et al 2007). It is interesting to recall that a similar situation occurred during the early days of PsaC, in which the psaC gene in chloroplasts was initially annotated as fdx1, a bacterial dicluster ferredoxin.…”
Section: Pshbi and Pshbii The Proteins Harboring The F A And F B Clumentioning
confidence: 65%
See 1 more Smart Citation
“…Different preparation procedures suggested either an F A /F B -type protein (Lin et al 1995;Nuijs et al 1985;Heinnickel et al 2006Heinnickel et al , 2007 or a quinone as electron acceptor (Trost and Blankenship 1989). The quinone present in the membrane is menaquinone with MK9 as the dominant form (Trost and Blankenship 1989;Hiraishi 1989).…”
Section: Organization Of the Bioenergetic Electron Transfer Chain In mentioning
confidence: 99%